Reviewed book: Dalia STREIMIKIENE, Indre SIKSNELYTE-BUTKIENE, Tomas BALEZENTIS (2024), Low Carbon Transition: Sustainable Agriculture in the European Union, CRC Press, 320 p. - Streimikis, Justas (Transformations In Business & Economics, 2025)
Authors: Dalia STREIMIKIENE, Indre SIKSNELYTE-BUTKIENE, Tomas BALEZENTIS Authors’ Affiliation: Vilnius University, Lithuanian Centre for Social Sciences Title: LOW CARBON TRANSITION: SUSTAINABLE AGRICULTURE IN THE EUROPEAN UNION Subtitle: Monograph Year: 2024 Publisher: CRC Press Volume: 320 pages Type of publication: book Language: English ISBN: 9781032607900 For more information contact: dalia.streimikiene@khf.vu.lt